REPRESENTASI SIFAT-SIFAT TELADAN NABI MUHAMMAD MELALUI PENOKOHAN KIAI MOEKTI DALAM NOVEL SEBUAH SURAU KARYA ARTIE AHMAD - Nugraha, Shafwan; Kalsum, Rahma Sari; Supriatna, Agus (Seshiski: Southeast Journal of Language and Literary Studies, 2023)
The research undertakes a qualitative examination of the representation of Prophet Muhammad's qualities as an exemplary figure for the Islamic community through the characterization of one of the novel's protagonists titled "Sebuah Surau" by Artie Ahmad. Within this literary work, one of the main characters named Kiai Moekti is depicted as a religious scholar who establishes a small mosque (the character 'Aku') and serves as a mentor to other main characters. The study on this literary piece employs a structural approach, revealing story facts. Data collection involves close reading techniques and note-taking. The research findings divulge that within the novel "Sebuah Surau," the character Kiai Moekti is portrayed as a religious leader who endeavors to practice his faith's teachings, notably by internalizing and embodying the characteristics of Prophet Muhammad as a role model for the Islamic community. These qualities manifest in his diligence in studying and disseminating Islamic teachings (tabligh), speaking the truth (shiddiq), maintaining trustworthiness (amanah), and possessing a broad and profound understanding of religious knowledge (fathanah).